تطبيقات على نمذجة جدران القص في الأبنية العالية - جحجاح غاندي; علي غسان شيخ; ميهوب أحمد (Latakia University Journal -Engineering Sciences Series, 2019)
‘تعتمد فرضيات مختلفة في تشكيل النماذج التحليلية للعناصر الإنشائية في الأبنية العالية، و يتعلق نوع النموذج بشكل وحجم المنشأ الحقيقي وبمرحلة التصميم التي ‘ينجز من اجلها التحليل .وعند نمذجة المنشآت العالية يتم تمثيل العناصر الإنشائية الأساسية فقط مثل جدران القص والإطارات والنوى والبلاطات، بعناصر إنشائية بسيطة وبديلة مكونة من عناصر جائزية أو عناصر سطحية. يعرض هذا البحث الفرضيات الأكثر شيوعا ًوالمبادئ والتقنيات المستخدمة في النمذجة، ويشمل على دراسة تحليلية لجداري قص مختلفين ( WI و WII) كل منهما معرض لحمولة أفقية منتظمة، ويحوي صفا شاقوليا من الفتحات المنتظمة، وتتم نمذجته بخمس طرق مختلفة. وتهدف هذه الدراسة لتحديد تأثير شكل النماذج على قيم الانتقالات الأفقية الحاصلة فيها ، و‘تحدد لكل من الجدارين النموذج الأكثر دقة في تمثيله. This paper presents the most commonly assumptions, principles, and techniques employed in forming an analytical models for structural members in tall building. The type of model relates to the type and size of structure and the stage of design for which the analysis is made. In modeling tall structures for analysis, it is usual to represent only the main structural members like shear walls, frames, cores, and slabs by equivalent simple structural members of beams or membrane elements. This research includes an analytical study for two different shear walls (WI & WII ) everyone of them is subjected to uniform horizontal load ,and has vertical row of regular openings , and modeled by five different models . This study seeks to identify the influence of type model on its horizontal displacements, and to determine for every shear wall the most accurate model in representing it.